2013
DOI: 10.5858/arpa.2012-0100-cp
|View full text |Cite
|
Sign up to set email alerts
|

Utilization of Stat Test Priority in the Clinical Laboratory: A College of American Pathologists Q-Probes Study of 52 Institutions

Abstract: Context.-Utilization of stat testing priority is a balance between safe, efficient patient management and resource expenditure.Objective.-To determine the rate of stat testing, compare rates among institutions, and determine the distribution of turnaround time expectations for different turnaround time priorities.Design.-During a 7-day period, participants prospectively determined the total number of chemistry, hematology, and coagulation billable tests from inpatients and emergency department patients. Among … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
10
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 18 publications
2
10
0
Order By: Relevance
“…The management team of the study examined patient LOS and found 60-70% of the 150 patient visits per day underwent laboratory testing. Although our Lab TAT goal for stat testing is 60 minutes, consistent with other labs in North America [8, 11-12], the audited 90 th percentile TAT (Lab TAT90; the time for 90% of laboratory tests to be complete) was consistently greater than 80 minutes. Laboratory TAT for ED patients was targeted for process improvement.…”
Section: Introductionsupporting
confidence: 61%
See 1 more Smart Citation
“…The management team of the study examined patient LOS and found 60-70% of the 150 patient visits per day underwent laboratory testing. Although our Lab TAT goal for stat testing is 60 minutes, consistent with other labs in North America [8, 11-12], the audited 90 th percentile TAT (Lab TAT90; the time for 90% of laboratory tests to be complete) was consistently greater than 80 minutes. Laboratory TAT for ED patients was targeted for process improvement.…”
Section: Introductionsupporting
confidence: 61%
“…The primary outcome was 90 th percentile test completion from specimen receipt in the lab to the result being reported (In-Lab-TAT90), a better indicator of laboratory performance than mean or median TAT [8, 11]: it captures much of the modifiable outlier effect and represents a standard of consistency required for ED care [23]. Survival analysis was used to determine the In-Lab-TAT90 and 95% confidence interval (CI) for each analyte.…”
Section: Methodsmentioning
confidence: 99%
“…Reduction of excessive stat order requests supports safe and efficient patient care 20,21 and may reduce laboratory costs. 22 Further, the study has potential implications for improving patient-centeredness of blood draw practices for hospitalized patients. Although we acknowledge that midnight may not be the best time for patients, the trial of midnight blood draws questioned the rationality of early morning blood draws.…”
Section: Discussionmentioning
confidence: 98%
“…The number of institutions participating in the studies listed in Table 4 ranged from 151 to 630; however, other studies have had participants from more than 900 institutions 8 or from as few as 52 institutions. 9 In these examples, the size of the databases ranged from 623 different practice patterns for notification of a test critical value to more than 18 million units of crossmatched blood in the blood utilization study.…”
Section: Methodsmentioning
confidence: 99%